1998
DOI: 10.1073/pnas.95.2.691
|View full text |Cite
|
Sign up to set email alerts
|

Rapid noninvasive detection of experimental atherosclerotic lesions with novel 99m Tc-labeled diadenosine tetraphosphates

Abstract: The development of a noninvasive imaging procedure for identifying atherosclerotic lesions is extremely important for the clinical management of patients with coronary artery and peripheral vascular disease. Although numerous radiopharmaceuticals have been proposed for this purpose, none has demonstrated the diagnostic accuracy required to replace invasive angiography. In this report, we used the radiolabeled purine analog, 99m Tc diadenosine tetraphosphate (Ap 4 A; AppppA, P 1 ,P 4 -di(adenosine-5)-tetraphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…19 A second approach has used radiolabeled peptides or small nonpeptide ligands. Atherosclerotic lesions in rabbits have been targeted with radiolabeled purine analogs, 20 cholesteryl ester analogs, 21 or oligopeptide fragments of apolipoprotein B. 22 Recently, 99m Tc-labeled annexin-V was used to detect cardiac allograft rejection and apoptosis.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…19 A second approach has used radiolabeled peptides or small nonpeptide ligands. Atherosclerotic lesions in rabbits have been targeted with radiolabeled purine analogs, 20 cholesteryl ester analogs, 21 or oligopeptide fragments of apolipoprotein B. 22 Recently, 99m Tc-labeled annexin-V was used to detect cardiac allograft rejection and apoptosis.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…We have shown rapid and high accumulation of 99m Tcconjugated by chelation adenosine nucleotide polyphosphates in inflamed atherosclerotic plaques (2). In addition, a closely related analog, P 2 ,P 3 -mono[ 18 F]fluoromethylene diadenosine-5Ј,5ٞ-P 1 ,P 4 -tetraphosphate ([ 18 F]AppCHFppA), which is an 18 Flabeled molecular probe (9), may be preferable because it is more securely attached by covalent linkage to the parent compound and accumulates selectively in atherosclerotic lesions, thereby allowing the noninvasive characterization of plaque inflammation with positron-emission tomography (PET) imaging.…”
mentioning
confidence: 99%
“…In this study, we evaluate the imaging capabilities of positron-emission tomography (PET) with P 2 ,P 3 -[ 18 O ur previous findings with 99m Tc-conjugated diadenosine-5Ј,5ٞ-P 1 ,P 4 -tetraphosphate (Ap 4 A) and P 2 ,P 3 -monochloromethylene diadenosine-5Ј,5ٞ-P 1 ,P 4 -tetraphosphate (AppCHClppA) in a rabbit model indicated rapid, high accumulation of both diadenosine tetraphosphate analogs in the atherosclerotic abdominal aorta and demonstrated up-regulation of purine receptors in experimental atherosclerotic lesions, suggesting the potential for using such labeled analogs for noninvasive detection of plaque formation (1,2). The atherogenic process involves sequestration of partially oxidized lipids in the vessel wall (3,4), leading to endothelial injury that promotes adherence of mononuclear cells and platelets and contributes to phenotypic transformation of medial smooth muscle cells (SMCs) from adult to embryonic forms.…”
mentioning
confidence: 99%
“…9 It has been proposed that upregulation of P2Y receptors is a potential diagnostic indicator for the early stages of atherosclerosis. 10 A direct pathological role of P2RY2 is reinforced by recent evidence 11 showing that the upregulation and activation of P2RY2 in rabbit arteries mediate the intimal hyperplasia that accompanies atherosclerosis. Guns et al 12 found that in the aorta of P2Y2-knockout mice, endothelium-dependent relaxation by ATP was inhibited, showing the role of P2RY2 in endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 76%